Perbedaan Asupan Tambahan Ibu Menyusui di Wilayah Pedesaan dan Perkotaan dalam Upaya Meningkatkan Produksi ASI - Nafiisah, Adilah; Ayu Wardani, Aradea Putri; Syahira, Fahriah Firda; Kania, Kaela Rahma; Tri Agus Sinaga, Yanti Hosianna (Universitas Negeri Malang, 2024)
Mother's milk (breast milk) is the best food for infants because it has preeminence and unique nutritional value over other sources of nutrition. Breast milk production (breast milk) may increase or decrease depending on breast gland stimulation, which one of the factors affecting breast production is the nutritional status of the mother, if the maternal diet continues to fail to meet sufficient nutrition, the mammalian glands in the breasts will not work perfectly and affect breast production. People's eating habits are affected by various factors, such as cultural social factors. Generally in rural areas, belief in foods that may otherwise hinder or increase secretion. As for urban dietary options, mothers may also consider taking additional supplement when needed. The study aims to find out the difference in breast-feeding consumption in rural and urban areas. The research design used is qualitative research using a string of phenomena. Research is conducted using methods of in-depth interviews of informants. Studies indicate that there is a variation in the type of additional intake consumed. In cities it is more likely to take supplements, vitamins and breast milk-stimulating drink, while in the countryside it eats natural intake, such as herbs and vegetables.